Leadership in a race based mentoring program: a case study of the program entitled “Can We Talk” - Butler, Craig D, II (Kansas State University, 2015)
This qualitative case study explored the role of leadership in a mentoring program designed to work with students of color. Specifically, an instrumental case study was used to explore the leadership of the “Can We Talk” mentoring program. Utilizing the framework of Critical Race Theory and themes related to the current status of students of color along the with the concept of school culture, the purpose of this study was to explore the leadership of a program “Can We Talk” designed to work with students of color in a majority White high school located in the Midwest. This purpose was also driven by the rationale that districts and schools due to increased accountability measures have to incorporate different strategies to meet the academic and social needs of all students. Mentoring programs are one of the strategies gaining momentum in education, especially for students who come from marginalized socio-economic, ethnic, and racial groups. The findings indicated that the “Can We Talk” program was implemented into this school setting based on interest convergence. The principal needed the program in order to meet accountability measures such as adequate yearly progress. The founders of the “Can We Talk” mentoring program had an interest of increasing the academic and social opportunities for the students of color at this school setting. Furthermore, the findings indicate that the “Can We Talk” program was successful based on the mentors being able to share their experiences with the mentees, attract students from other gender, ethnic and racial groups, and increase the academic and social opportunities of the mentees by creating a shared voice. The implications of this study includes questions about the ways mentoring programs for students of color are implemented and maintained in majority White school settings. Therefore, this study raises the question about the role of school administrators, founders of mentoring programs, teachers, and the rest of the school community in terms of implementing, maintaining, and supporting programs designed to support the needs of children of color.
Keywords: Mentoring; Critical Race Theory; Students of color; Case study; Role of school administrator; Educational leadership; Educational leadership (0449); Higher Education Administration (0446); Multicultural education (0455)